COMPARISON OF THE EFFECTIVENESS OF RADIATION SHIELD WALL BETWEEN LEAD-LAYERS AND PLASTERING BRICK-LAYERS - Ardi Soesilo Wibowo; Edy Cahyono; Retno Sri Iswari; Kholik Al Amin; Marichatul Jannah (Poltekkes Kemenkes Semarang, 2022)
The rate of exposure to X-ray radiation on the radiation shielding wall at the Laboratory 3 of Radiology Study Program Purwokerto Diploma Three Program has been analyzed, to find out the difference in the effectiveness of the radiation shielding wall between a 10 cm thick Lead (2 mm) coated partition and a 28 cm thick stucco brick wall. Measurements were made using a radiation source, namely a mobile unit X-ray machine with a Fluke survey meter radiation measuring instrument. Measurement of the rate of exposure to X-ray radiation is carried out by adjusting the distance of the radiation source with the radiation shield wall from 100 cm, 150 cm and 200 cm and taken from 5 measurement points that represent the radiation shield wall. The measurement results show that measurement point C produces the highest radiation exposure rate and measurement point A produces the lowest radiation exposure rate for Do and D. There is a radiation exposure rate of more than 1 μSv/Hr after passing through a 10 cm thick Lead-coated partition wall (2 mm) at a distance of 100 cm to 150 cm. Radiation shielding walls of walls covered with stucco bricks with a thickness of 28 cm were more effective than partitions covered with lead (2 mm) with a thickness of 10 cm. It is necessary to pay attention to aspects of radiation protection, the use of a mobile unit X-ray machine in placing the X-ray tube in the direction of the X-ray tube and, the radiation source distance of at least 2 meters from the lead-coated partition radiation wall.